SATU DEKADE PEMBANGUNAN SUMBER DAYA MANUSIA DI WILAYAH PESISIR: CAPAIAN DAN TANTANGAN (KASUS PULAU MAPUR, KABUPATEN BINTAN) - NFN Widayatun (Jurnal Kependudukan Indonesia, 2016)
The coastal areas of Indonesia are rich of natural resources. However, the resources have not been utilized optimally due to several factors, including the low quality of human resources. People who live in coastal areas generally live with low economic conditions as indicated by high incidence of poverty in this region. The economic activity of population who lives in coastal areas, particularly fishermen, depends on the utilization of the natural resources with low technology and limitation of capital. To improve the quality of human resources and reduce poverty in coastal areas, various community empowerment programs have been conducted. This article aims to examine the achievement of community empowerment programs and its challenge to achieve the program goals in Mapur Island, one of coastal area in Bintan Regency. The data used for this study are baseline studies of socio-economic aspects of coral reefs in Mapur Village conducted by PPK-LIPI in 2005 and 2015. The results shows that after a decade of community development programs implemented in the island of Mapur, the economic conditions of the population has improved as indicated by the increase of household income. Sources of income for the population also become more varying since economic opportunities open up more in the field of trade, services and transportation as a result of the development programs in coastal areas. However, the condition of human resources as indicated by educational level has not achieved the expected results. The education level of the population does not show significant changes over a decade. School dropout rates are quite high and the majority of the population only completed elementary school.